Access to hip and knee arthroplasty in England: commissioners' policies for body mass index and smoking status and implications for integrated care systems - Joanna McLaughlin; Joshua Elsey; Ruth Kipping; Amanda Owen-Smith; Andrew Judge; Hugh McLeod (BMC, 2023)
Abstract Background Commissioning policies are in place in England that alter access to hip and knee arthroplasty based on patients' body mass index and smoking status. Our objectives were to ascertain the prevalence, trend and nature of these policies, and consider the implications for new integrated care systems (ICSs). Methods Policy data were obtained from an internet search for all current and historic clinical commissioning group (CCG) hip and knee arthroplasty policies and use of Freedom of Information (FOI) requests to each CCG. Descriptive analyses of policy type, explicit threshold criteria and geography are reported. Estimates were made of the uptake of policies by ICSs based on the modal policy type of their constituent CCGs. Results There were 106 current and 143 historic CCGs in England at the time of the search in June 2021. Policy information was available online for 56.2% (140/249) CCGs. With the addition of information from FOIs, complete policy information was available for 94.4% (235/249) of CCGs. Prevalence and severity of policies have increased over time. For current CCGs, 67.9% (72/106) had a policy for body mass index (BMI) and 75.5% (80/106) had a policy for smoking status for hip or knee arthroplasty. Where BMI policies were in place, 61.1% (44/72) introduced extra waiting time before surgery or restricted access to surgery based on BMI thresholds (modal threshold: BMI of 40 kg/m2, range 30-45). In contrast, where smoking status policies were in place, most offered patients advice or optional smoking cessation support and only 15% (12/80) introduced extra waiting time or mandatory cessation before surgery. It is estimated that 40% of ICSs may adopt a BMI policy restrictive to access to arthroplasty. Conclusions Access policies to arthroplasty based on BMI and smoking status are widespread in England, have increased in prevalence since 2013, and persist within new ICSs. The high variation in policy stringency on BMI between regions is likely to cause inequality in access to arthroplasty and to specialist support for affected patients. Further work should determine the impact of different types of policy on access to surgery and health inequalities.